Gas heating and plasma chemistry in low-pressure CO2 plasmas - Yang Liu; Tiago Silva; Tiago C. Dias; Pedro Viegas; Xiangen Zhao; Yaping Du; Junjia He; Vasco Guerra (Journal of CO2 Utilization)
We develop a self-consistent kinetic model to simulate the evolution of species and energy transfers in low-pressure CO2 plasmas. This model couples the electron, vibrational and chemical kinetics with the gas thermal balance equation, providing a comprehensive framework for understanding CO2 plasmas. The kinetic model is thoroughly benchmarked and validated by comparison its predictions with reported simulation and experimental data on CO2 DC glow discharges, operating at pressures 1–5 Torr, discharge currents of tenths of mA, and tube radius of 1 cm. The results show that the energy released from electronic and vibrational excitation of CO2 dominates the gas heating at the early stage of the discharge. However, as the discharge progresses and reaches steady-state, following CO2 dissociation, the de-excitation of electronically excited states of the products and the vibrational-translational exchanges of the CO vibrational state significantly contributes to the gas heating. Additionally, the quenching of excited states at the wall is both a major destruction pathway for these species and a contributor to the gas heating. This study provides a comprehensive perspective to the microscopic reactions and macroscopic parameters in CO2 plasmas, which can inform optimization strategies for industrial applications.